Life after formal employment: A comparative study of female ‘garments and textiles’ and ‘all other’ factory’ workers in Sri Lanka - Hancock, Peter; Adusei-Asante, Kwadwo; Georgiou, Jonathan; Boafo, Isaac (Advances in Social Sciences Research Journal, 2018)
This paper compares the post-employment social, political and economic profiles of women previously employed in Sri Lanka’s formal manufacturing sector. We surveyed 1031 female respondents, consisting of 775 former garment and textile (G&T) and 256 ‘all other’ (‘other’) former factory workers. Results showed that women who had worked in G&T factories were significantly more likely to have reported bringing back ‘useful’ skills and knowledge upon their return home. However, those previously employed in ‘other’ factories were 1.49 times more likely to report feeling greater acceptance from communities; as well as slightly higher rates of political participation. Regardless of such differences, a significant proportion across both groups shared a sense of self-confidence – even having set up their own businesses or now owning properties since leaving formal employment. Thus, contrary to the negative portrayal of factory work in Sri Lanka and the purported ‘plight’ of its largely female labor force, our research has found that most women – regardless of prior workplace – had retained and built upon their socio-economic capital across many important aspects of their lives.